Zora alpina Kulczyński, 1915 (Araneae: Miturgidae): description of the male, redescription of the female - Mazzoleni, Federico; Pantini, Paolo; Pedrotti, Luca; Gobbi, Mauro (Zootaxa, 2016)
Zora Koch, 1847 is a small genus distributed in the Holarctic region. The genus comprises 16 species, 14 of them distributed in the Palaearctic region and two from the Neartic (World Spider Catalog 2016). The European fauna includes 11 species (Nentwig et al. 2016), 8 of which are present in Italy (Pantini & Isaia 2016). Zora has historically been placed in several different families, but is now in the Miturgidae Simon, 1886 following the phylogenetic analyses of Ramirez (2014).